A review of Mpox: Biological characteristics, epidemiology, clinical features, diagnosis, treatment, and prevention strategies - Lin Jiang; Ailan Xu; Lin Guan; Yong Tang; Guangshuai Chai; Junya Feng; Yueqi Wu; Maochen Li; Chuxie Zhang; Xiaojing Liu; Xiaolong Xu; Qingquan Liu; et al. (Exploration)
Abstract The outbreak of monkeypox virus (MPXV) was declared a Public Health Emergency of International Concern (PHEIC) by the World Health Organization (WHO), and the zoonotic disease caused by viral infection was renamed as “Mpox” on November 28, 2022. Currently, there is no approved vaccine or specific antiviral treatment for Mpox, and a main preventive strategy against MPXV infection remains the smallpox vaccine. Although there was an emergency use authorization (EUA) of Brincidofovir and Tecovirimat for the clinical treatment of clade II Mpox, while Tecovirimat failed to reduce the duration of Mpox lesions among patients infected with clade I Mpox in the Democratic Republic of the Congo (DRC). Therefore, it is still an urgent need to develop an effective medication. This review aims to enhance the understanding of Mpox and contribute to its prevention and treatment strategies, it provides a systemic introduction of the biological and epidemiological characteristics of MPXV, the clinical feature and diagnosis of Mpox, as well as treatment and prevention strategies, which will improve the comprehension about MPXV and offer potential strategies for clinical treatment.